Ontogeny-specific induction of the KMT2A::AFF1-fusion drives development of a distinct CD24 positive pre-leukemic state - Calderón, Ariana S.; Ghazanfari, Roshanak; Masoumi, Zahra ; 0000-0002-6685-4127; Kharazi, Shabnam; Palo, Sara; Lang, Stefan ; 0000-0002-0854-2328; Žemaitis, Kristijonas; Eldeeb, Mohamed; Subramaniam, Agatheeswaran; Soneji, Shamit; Stam, Ronald W.; Bryder, David; et al. (Leukemia, 2025)
Infant Acute Lymphoblastic Leukemia (ALL) driven by the KMT2A::AFF1 onco-fusion is an aggressive, poor prognosis disease with few co-operative mutations. The fusion originates in utero, yet the embryonic initiating steps of disease development remain poorly understood. Here, we present a novel murine KMT2A::AFF1 model, that provides key insights into KMT2A::AFF1 pre-leukemia, relevant to human disease. The model enables precise oncogene induction, and upon targeting hematopoietic stem and progenitor cells (HSPCs) a selective negative impact on proliferation of hematopoietic stem cells (HSCs) was observed, regardless of developmental state during induction. However, a unique CD24+PreProB subset expanded exclusively within the KMT2A::AFF1 embryonic context. This population was absent when targeting lymphoid progenitors, highlighting the importance of the cell of origin for leukemic development. The CD24+PreProB subset displayed key features of pre-leukemic stem cells, including lineage plasticity and aberrant engraftment ability. In line with their pre-malignant phenotype, single-cell transcriptomics revealed a signature consistent with stemness, and notable, up-regulation of Hmga2, a regulator of self-renewal. The signature was critically transferable to human KMT2A::AFF1 patients. Furthermore, given that CD24 is a potential therapeutic target, our findings uncover a distinct embryonic pre-leukemic state with direct relevance to human disease. (Figure presented.)
Publisher Copyright: © The Author(s) 2025.